MEMBANGUN DESA MELEK HUKUM : PENYULUHAN HUKUM DAN SOSIALISASI BANTUAN HUKUM SECARA CUMA-CUMA - Krista Yitawati; Angga Pramodya Pradhana; Mohammad Choirul Anam (JURNAL DAYA-MAS, 2025)
The purpose of writing this community service journal is to provide education to the community about the law in order to increase legal awareness in the community and provide socialization regarding the procedures and requirements for obtaining free legal aid for the poor. The method used is to conduct legal counseling and socialization regarding the free legal aid program in Pilangbango Village, Kartoharjo District, Madiun City. This activity is a real manifestation of the commitment of the government, academics and all stakeholders in building a just society and is a community service program from Merdeka University of Madiun. This activity provides an important contribution in solving community problems in accessing information to obtain free legal aid and eroding negative old assumptions and mindsets that have been built and influence actions, especially for the underprivileged community to obtain opportunities for justice and legal protection to access affordable services. The provision of Legal Aid to citizens is an effort to fulfill and at the same time as an implementation of a legal state that recognizes and protects and guarantees the basic rights of citizens to the need for access to justice and equality before the law.